RINTISAN SEKOLAH BERSTANDAR INTERNASIONAL:Antara Cita & Fakta - Ma’arif, Syamsul (WALISONGO, 2011)
Abstract Â  This paper is the result of research on junior school of RSBI 2 Semarang. By using qualitative descriptive research methods and approaches case can be concluded that no other RSBI founding purpose is only to get to quality education in Indonesia and are able to compete at international level. Moreover, the fact that Indonesia is part of the life of a globalized world, it is in harmony with the global demands should be considered in order to have an accredited educational international. Where the quality of our educational institution recognized internationally. Indonesia does not need education âembarrassedâ let alone to be arrogant in the face of the criteria used at the international level. Although in practice RSBI, faces a number of problems both economic, psychological, cultural and governance management. Â  *** Artikel ini merupakan hasil penelitian di SMP RSBI 2 Semarang. Dengan menggunakan pendekatan deskriptif kualitatif dapat disimpulkan bahwa tujuan pendirian RSBI tidak lain adalah hanya untuk mendapatkan pendidikan yang berkualitas di Indonesia dan mampu bersaing di tingkat internasional. Selain itu, fakta bahwa Indonesia adalah bagian dari kehidupan dunia yang mengglobal. Selaras dengan tuntutan global itu adalah harus dipertimbangkan dalam rangka untuk memiliki pendidikan yang terakreditasi secara internasional. Dimana kualitas lembaga pendidikan kita diakui secara internasional. Meskipun dalam prakteknya RSBI, menghadapi sejumlah masalah baik manajemen ekonomi, psikologis, budaya, dan pemerintahan. Â  Keywords: cita, praksis, problematika RSBI